METODE KONFRONTATIF DAN URGENSINYA DALAM UPAYA MENGUNGKAP KEPALSUAN RIWAYAT - Hariono, Duwi (LPPM IAIN Kediri, 2023)
Hadith is the second authoritative source of law after the Koran. The authority of hadith is legalized by the statements of the Koran in various verses. This authoritative status of hadith then creates new challenges and problems, namely that it is used by irresponsible parties to falsify it for certain interests. Forgery of hadith is a very serious problem because it poses a threat to the integrity of Islam. This article discusses the urgency of confrontational understanding as a method for exposing historical falsities.Confrontational understanding here refers to an approach that confronts -especially- the hadith with the Qur'an. This is done by utilizing the principles of the characteristics of fake hadith as a basis for analysis. It is hoped that the success of the confrontational method will provide new insights into the study of hadith, help identify falsification of hadith, and maintain the authenticity of Islamic teachings.Through confrontational method analysis, it is hoped that this article can make a positive contribution in understanding, identifying and overcoming false hadith, so that Muslims can maintain the authenticity of their religious teachings. By highlighting the seriousness of hadith falsification, this article invites readers to understand the complexity of this problem and respond with careful and critical confrontational methods